Sustainability and economic evaluation of Microalgae - Natanamurugaraj, Govindan; Gaanty Pragas, Maniam; M. M., Yusoff; Mohd Hasbi, Ab. Rahim (2019)
The enhancement of the atmospheric greenhouse effect due to the increase in the atmospheric greenhouse gases is often considered as responsible for global warming. Several analyses have been made on the key issues of scientific understanding of contemporary global climate change. Air pollution are directly related with climate changes and it has been increasing the potential of ecosystems and human health risks. The policy and scientific assessments to climate change included the consideration of the risks and expressed climatic events. Microalgae has been identified as one of the potential feedstock for various bio product production since its cultivation requires less cropland compared to conventional oil crops and the high growth rate. The potential of microalgae to produce multiple bio based products in a biorefinery framework. The integration of emerging biorefineries is potential solution to mitigate the threat of climate change, global warming and food insecurity.